Βιβλιοκρισία:Ecclesiastical History and Nikephoros Kallistou Xanthopoulos, Proceedings of the International Symposium, Vienna, 15th-16th December 2011, ed. Chr. GASTGEBER and S. PANTEGHINI [Veröffentlichungen zur Byzanzforschung, 37], Wien 2015, 184 σελ. - ΚΙΑΠΙΔΟΥ Ειρήνη-Σοφία (Byzantina Symmeikta, 2017)
Βιβλιοκρισία:Ecclesiastical History and Nikephoros Kallistou Xanthopoulos, Proceedings of the International Symposium, Vienna, 15th-16th December 2011, ed. Chr. GASTGEBER and S. PANTEGHINI [Veröffentlichungen zur Byzanzforschung, 37], Wien 2015, 184 σελ.